2018
DOI: 10.1016/j.specom.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visual cues on head and eye movements during listening tasks in multi-talker audiovisual environments with animated characters

Abstract: Recent studies of hearing aid benefits indicate that head movement behavior influences performance. To systematically assess these effects, movement behavior must be measured in realistic communication conditions. For this, the use of virtual audiovisual environments with animated characters as visual stimuli has been proposed. It is unclear, however, how these animations influence the head-and eye-movement behavior of subjects. Here, two listening tasks were carried out with a group of 14 young normal hearing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…To be able to control the realism of head movement, the experimental factors influencing the movement need to be identified. In that regard, Hendrikse et al (2018) found that subjects moved their heads and eyes much less in turn-taking conversations if no visual stimulation was provided. Furthermore, Hendrikse et al (2018) showed that subjects changed their movement behavior dependent on the head and gaze behavior of animated characters used as simulated conversation partners.…”
Section: Requirements For Reflecting Real-life Communication In the Lmentioning
confidence: 98%
See 4 more Smart Citations
“…To be able to control the realism of head movement, the experimental factors influencing the movement need to be identified. In that regard, Hendrikse et al (2018) found that subjects moved their heads and eyes much less in turn-taking conversations if no visual stimulation was provided. Furthermore, Hendrikse et al (2018) showed that subjects changed their movement behavior dependent on the head and gaze behavior of animated characters used as simulated conversation partners.…”
Section: Requirements For Reflecting Real-life Communication In the Lmentioning
confidence: 98%
“…In that regard, Hendrikse et al (2018) found that subjects moved their heads and eyes much less in turn-taking conversations if no visual stimulation was provided. Furthermore, Hendrikse et al (2018) showed that subjects changed their movement behavior dependent on the head and gaze behavior of animated characters used as simulated conversation partners. This shows that measures of head and eye movements may be used as a metric to assess experimental paradigms and their level of ecological validity*.…”
Section: Requirements For Reflecting Real-life Communication In the Lmentioning
confidence: 98%
See 3 more Smart Citations